Targeting Phosphoinositide-3-Kinase-δ with Theophylline Reverses Corticosteroid Insensitivity in Chronic Obstructive Pulmonary Disease - To, Yasuo; Ito, Kazuhiro; Kizawa, Yasuo; Failla, Marco; Ito, Misako; Kusama, Tadashi; Elliott, W. Mark; Hogg, James C.; Adcock, Ian M.; Barnes, Peter J. (American journal of respiratory and critical care medicine, 2010)
Patients with chronic obstructive pulmonary disease (COPD) show a poor response to corticosteroids. This has been linked to a reduction of histone deacetylase-2 as a result of oxidative stress and is reversed by theophylline. To determine the role of phosphoinositide-3-kinase-delta (PI3K-δ) on the development of corticosteroid insensitivity in COPD and under oxidative stress, and as a target for theophylline. Corticosteroid sensitivity was determined as the 50% inhibitory concentration of dexamethasone on tumor necrosis factor-α-induced interleukin-8 release in peripheral blood mononuclear cells from patients with COPD (n = 17) and compared with that of nonsmoking (n = 8) and smoking (n = 7) control subjects. The effect of theophylline and a selective PI3K-δ inhibitor (IC87114) on restoration of corticosteroid sensitivity was confirmed in cigarette smoke-exposed mice. Peripheral blood mononuclear cells of COPD (50% inhibitory concentration of dexamethasone: 156.8 ± 32.6 nM) were less corticosteroid sensitive than those of nonsmoking (41.2 ± 10.5 nM; P = 0.018) and smoking control subjects (47.5 ± 19.6 nM; P = 0.031). Corticosteroid insensitivity and reduced histone deacetylase-2 activity after oxidative stress were reversed by a non-selective PI3K inhibitor (LY294002) and low concentrations of theophylline. Theophylline was a potent selective inhibitor of oxidant-activated PI3K-δ, which was up-regulated in peripheral lung tissue of patients with COPD. Furthermore, cells with knock-down of PI3K-δ failed to develop corticosteroid insensitivity with oxidative stress. Both theophylline and IC87114, combined with dexamethasone, inhibited corticosteroid-insensitive lung inflammation in cigarette-smoke-exposed mice in vivo. Inhibition of oxidative stress dependent PI3K-δ activation by a selective inhibitor or theophylline provides a novel approach to reversing corticosteroid insensitivity in COPD.